Evolutionarily diverse determinants of meiotic DNA break and recombination landscapes across the genome - Fowler, Kyle R.; Sasaki, Mariko; Milman, Neta; Keeney, Scott; Smith, Gerald R. (Genome Research, 2014)
Fission yeast Rec12 (Spo11 homolog) initiates meiotic recombination by forming developmentally programmed DNA double-strand breaks (DSBs). DSB distributions influence patterns of heredity and genome evolution, but the basis of the highly nonrandom choice of Rec12 cleavage sites is poorly understood, largely because available maps are of relatively low resolution and sensitivity. Here, we determined DSBs genome-wide at near-nucleotide resolution by sequencing the oligonucleotides attached to Rec12 following DNA cleavage. The single oligonucleotide size class allowed us to deeply sample all break events. We find strong evidence across the genome for differential DSB repair accounting for crossover invariance (constant cM/kb in spite of DSB hotspots). Surprisingly, about half of all crossovers occur in regions where DSBs occur at low frequency and are widely dispersed in location from cell to cell. These previously undetected, low-level DSBs thus play an outsized and crucial role in meiosis. We further find that the influence of underlying nucleotide sequence and chromosomal architecture differs in multiple ways from that in budding yeast. DSBs are not strongly restricted to nucleosome-depleted regions, as they are in budding yeast, but are nevertheless spatially influenced by chromatin structure. Our analyses demonstrate that evolutionarily fluid factors contribute to crossover initiation and regulation.
10.1101/gr.172122.114